Effect of surgical margin width on prognosis in patients with single intrahepatic cholangiocarcinoma from a multicenter study - LIU Hongzhi, LIN Ziguo, HUANG Jianlong, ZHOU Weiping, CHENG Zhangjun, LOU Jianying, ZHENG Shuguo, BI Xinyu, WANG Jianming, GUO Wei, LI Fuyu, WANG Jian, ZHENG Yamin, LI Jingdong, CHENG Shi, LIU Jingfeng, ZENG Yongyi (Waike lilun yu shijian, 2021)
Objective To investigate the effect of wide surgical margin on the prognosis of patients with single intrahepatic cholangiocarcinoma (ICC) undergoing hepatectomy and the effect of microvascular invasion (MVI) on the treatment of hepatectomy with both wide surgical margin and narrow surgical margin. Methods From December 2011 to December 2017, the clinicopathological data of 302 patients with single ICC who underwent radical resection were retrospectively studied in 13 medical centers. According to the width of surgical margin, there were 126 patients (41.7%) in wide surgical margin group (≥1 cm) and 176 patients (58.3%) in narrow surgical margin group (<1 cm). Overall survival rate and disease-free survival rate of two groups were compared by Kaplan-Meier analysis. Subgroup analysis was conducted to compare the differences in prognosis of patients with different MVI. Results Using 1∶1 propensity score matching(PSM), 83 patients were in both wide surgical margin group and narrow surgical margin group, and there was no statistical difference in baseline data between two groups (all P>0.05). Disease-free survival rate in wide surgical margin group before PSM was significantly higher than that in narrow surgical margin group (P=0.005), while overall survival rate showed no statistically significant difference (P=0.053). After PSM, both overall survival rate and disease-free survival rate in wide surgical margin group were significantly higher than those in narrow surgical margin group (P<0.05). There was no statistically significant difference in both overall survival rate and disease-free survival rate among patients with MVI positive after liver resection with different surgical margins (P>0.05). In MVI negative group, however both overall survival rate and disease-free survival rate were significantly higher in the patients with wide surgical margin hepatectomy than in those with narrow surgical margin (P<0.05). Conclusions Wide surgical margin in hepatectomy can increase overall survival and disease-free survival in patients with single ICC, but does not improve prognosis when patients with MVI.